О сходимости решений вариационных неравенств с двусторонними препятствиями в перфорированных областей - Ковалевский А.А. (Український математичний журнал, 1992)
Conditions and the type of convergence of the solutions of elliptical variational inequalities with two-sided obstructions in perforated regions are established.